The Breast Cancer Susceptibility Gene BRCA2 Is Required for the Maintenance of Telomere Homeostasis - Min, Jaewon (American Society for Biochemistry and Molecular Biology, 2012)
Inactivating mutations in the breast cancer susceptibility gene BRCA2 cause gross chromosomal rearrangements. Chromosome structural instability in the absence of BRCA2 is thought to result from defective homology-directed DNA repair. Here, we show that BRCA2 links the fidelity of telomere maintenance with genetic integrity. Absence of BRCA2 resulted in signs of dysfunctional telomeres, such as telomere shortening, erosions, and end fusions in proliferating mouse fibroblasts. BRCA2 localized to the telomeres in S phase in an ATR-dependent manner, and its absence resulted in the accumulation of common fragile sites, particularly at the G-rich lagging strand, and increased the telomere sister chromatid exchange in unchallenged cells. The incidence of common fragile sites and telomere sister chromatid exchange increased markedly after treatment with replication inhibitors. Congruently, telomere-induced foci were frequently observed in the absence of Brca2, denoting activation of the DNA damage response and abnormal chromosome end joining. These telomere end fusions constituted a significant portion of chromosome aberrations in Brca2-deficient cells. Our results suggest that BRCA2 is required for telomere homeostasis and may be particularly important for the replication of G-rich telomeric lagging strands.